Prospective, Randomised Trial of Two Doses of rFVIIa (NovoSeven) in Haemophilia Patients with Inhibitors Undergoing Surgery - Shapiro, Amy D.; Gilchrist, Gerald S.; Hoots, W. Keith; Cooper, Herbert A.; Gastineau, Dennis A. (Thrombosis and Haemostasis, 1998)
Recombinant factor VIIa (rFVIIa; NovoSeven® ; Novo Nordisk) has proven efficacy in the treatment of haemophilic patients with inhibitors. This prospective, double-blind study compared rFVIIa (35 vs. 90 μg/kg) in the initiation and maintenance of haemostasis during and after elective surgery. Patients with inhibitors (FVIII, n = 26; FIX, n = 3) received rFVIIa immediately prior to incision; intraoperatively as needed; every 2 h for the first 48 h; and every 2-6 h for the following 3 days. Haemostasis was evaluated during surgery, at 0, 8, 24 and 48 h and 3, 4 and 5 days after wound closure. After day 5, open-label rFVIIa (90 μg/kg) was available for maintenance. Intraoperative haemostasis was achieved in 28/29 patients. All high-dose patients and 12/15 low dose patients had satisfactory haemostasis during the first 48 h. Twenty-three patients (13/14 high dose) successfully completed the study. Although the 35 μg/kg dose is probably sub-optimal for post-operative management, at least in major procedures, rFVIIa 90 μg/kg is an effective first-line option in surgery for patients with inhibitors.